Aspects of the anaerobic digestion of wattle tannins - Hurlow, Elton Lloyd (Rhodes University, Faculty of Science, Department of Chemistry, 1987)
The aqueous extract from the bark of the black wattle tree, (Acacia mearnsii De Wild)(1), is used extensively in the tanning industry for the production of sole and other heavy leathers as well as in lighter leathers and skins. The commercial extract is available in an easily dissolvable spray dried form and in deference to its genus name Mimosaceae is referred to in the trade as Mimosa(3). Mimosa extract consists primarily of high molecular weight polymeric flavonoid units which also constitutes the active tanning ingredient. Lower phenolics, gums and sugars or the so called "non-tannins" are present as impurities and contribute up to 40% to (3 ) the total mass of the extract.
Keywords: Tanneries -- Waste disposal